2008
DOI: 10.2169/internalmedicine.47.0579
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Encephalomyopathy Associated with Diabetes Mellitus, Cataract, and Corpus Callosum Atrophy

Abstract: A 44-year-old

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
2
0
2
Order By: Relevance
“…Increase in stain with the Gomori trichrome and oxidative stains in some small fibers, increased lipid content and suggestive electron microscopy changes also raised the possibility of a metabolic or, more specifically, mitochondrial cytopathy; however, this was not supported by CSF and plasma lactate levels which were normal, as were respiratory chain enzyme studies. Although callosal atrophy and cataracts [Oishi et al, 2008] as well as combined immunodeficiencies [Reichenbach et al, 2006; Kavadas et al, 2008] have been reported in association with genetic defects affecting the mitochondrial machinery, the entire sequence characteristic of Vici syndrome has not been described in association with any mitochondrial defect.…”
Section: Discussionmentioning
confidence: 99%
“…Increase in stain with the Gomori trichrome and oxidative stains in some small fibers, increased lipid content and suggestive electron microscopy changes also raised the possibility of a metabolic or, more specifically, mitochondrial cytopathy; however, this was not supported by CSF and plasma lactate levels which were normal, as were respiratory chain enzyme studies. Although callosal atrophy and cataracts [Oishi et al, 2008] as well as combined immunodeficiencies [Reichenbach et al, 2006; Kavadas et al, 2008] have been reported in association with genetic defects affecting the mitochondrial machinery, the entire sequence characteristic of Vici syndrome has not been described in association with any mitochondrial defect.…”
Section: Discussionmentioning
confidence: 99%
“…There are also many metabolic and genetic defined or undefined diseases that are associated with CC abnormalities. 12,13 In our study, associated genetic and metabolic diseases were identified in 17 patients (27.42%). Developmental abnormalities of CC may occur as an isolated lesion, but they are frequently associated with other cerebral malformations.…”
Section: Discussionmentioning
confidence: 58%
“…Die Ausfälle sind meist transient mit guter Remissionstendenz. Neben den klassischen phänotypischen Merkmalen, die das Akronym repräsentiert, präsentieren sich MELAS-Patienten häufig mit Manifestationen des Zentralnervensystems (Epilepsie, Myoklonien, zerebellärer Ataxie, migräneartigen Kopfschmerzen, psychiatrischen Auffälligkeiten, wie Verwirrtheit, Gedächtnisstörungen, Denkstörungen, Befindlichkeitsstörungen, Halluzinationen, oder kognitiven Defiziten bis hin zur Demenz [3]), des peripheren Nervensystems (Myopathie [4]), des Auges (Optikusatrophie [5], Retinopathie [6], Katarakt [3,5]), des Ohres (Taubheit bzw. akuter Hörverlust (Hörsturz) [7]), des endokrinen Systems (hypothalamische-hypophysäre Dysfunktion, Hypogonadismus, Infertilität, Diabetes, Hypoparathyroidismus, Kleinwuchs [8]), des kardiovaskulären Systems (Kardiomyopathie [9], Rhythmusstörungen, insbesondere Wolff-Parkinson-White-Syndrom [10], Herzbeuteltamponade [11], mitochondriale Angiopathie [4], akute Aortenruptur [12], linksventrikuläre Hypertrabekulierung [13]), des Magen-Darm-Traktes (Appetitlosigkeit, Übelkeit, Erbrechen, Blähungen, chronische Obstipation, intestinale Pseudoobstruktion [14,15]), der Nieren (Niereninsuffizienz durch Tubulopathie [5]), oder der Haut (Lipome, juckende, diffuse Erythemata, retikuläre Pigmentation, moderate Hypertrichose, seborrhoische Ekzeme, Atopie oder Vitiligo [16 -19]…”
unclassified
“…Myopathie (Ptose, Doppelbilder, CPEO, Paresen der Extremitäten, Muskelhypotonie, Dysarthrie, Muskelkrämpfe, rasche Ermüdbarkeit) [3,18] Polyneuropathie [64] Dysmorphismus Große ödematöse Hände [18] Hypertelorismus [18] Vorstehende Ohren [18] Auge Katarakt [3,5] Ohr Akuter Hörverlust (Hörsturz) [7] Innenohrschwerhörigkeit [18] Endokrinium Hypothyreose [65] Hypoparathyroidismus [66] Diabetes [61] Kleinwuchs [8,18] Herz Hypertrophe/dilatative Kardiomyopathie [9,67] Rhythmusstörungen (AF, WPW) [10,67] Herzbeuteltamponade [11] Linksventrikuläre Hypertrabekulierung [13] Gefäße Mitochondriale Angiopathie [4,68] Akute Aortenruptur [12] Gastrointestinaltrakt Appetitlosigkeit Übelkeit [15] Erbrechen [18] Blähungen [14] Chronische Obstipation [14] Intestinale Pseudoobstruktion [14] Niere Niereninsuffizienz durch Tubulopathie [5] Knochenmark Anämie [Finsterer, submitted] Haut Lipome [16 -18] Juckende, diffuse Erythemata [19] Retikuläre Pigmentation [19] Moderate Hypertrichose [19] Seborrhoisches Ekzem [19] Atopie oder Vitiligo [18,19] Lokales Melanoderma [18] sämtliche bekannte Abnormitäten, besonders aber Vorhofflimmern, Blockbildungen bzw. Zeichen der linksventrikulären Hypertrophie zeigen.…”
unclassified